The development of Brazilian women’s and gender studies: a bibliometric diagnosis - Hoppen, Natascha Helena Franz; Vanz, Samile Andréa de Souza (Scientometrics, 2023)
This study analyzes the characteristics and development of Brazilian research on women’s and gender studies using a new comprehensive data source that is still hardly explored in bibliometric studies called 1Findr. The search expression forms a part of a methodological proposition for similar studies, based on the literature review of other analogous studies and on the historical and current characteristics of Brazil. We analyzed 31,609 Brazilian articles on women’s and gender studies based on bibliometric indicators including activity, collaboration, and thematic association, with excerpts from the 1970s to 2019. Our results show that, initially, research was linked to the health sciences and was carried out in institutions in the Southeast and South of the country; however, this trend started changing since the 1990s, when two journals specialized in the area were first developed in Brazil and when researchers in the human and social sciences started working with this subject. Since then, the volume of articles, collaboration, and research has grown throughout the country, although production is still concentrated in the Southeast and South. Federal public universities are the main research actors, and researchers prioritize national journals and the Portuguese language. However, the main characteristic, which increases over time, is plurality: in relation to science in general and to other areas of Brazilian research, women’s and gender studies present a greater plurality in terms of its publication characteristics, for example, in relation to the amount and percentage of languages. Plurality is also observed in the fact that, over the years, researchers from new disciplines have started to publish on gender studies, making the area more and more inter- and multidisciplinary, and also consolidating it scientifically, in the sense that it has become a subject of interest for all areas of research. Its presence in journals with the best ratings in the Brazilian research system supports the understanding that this is a scientifically consolidated area. In contrast, despite its continuous growth, collaboration is a rare phenomenon, and specific characteristics of studies carried out with foreign partners can be observed. Collaboration clusters among national institutions are characterized, among other factors, by their geographic proximity and the central role of major universities, such as Universidade de São Paulo, and others associated with the history of the area in the country, such as Universidade de Campinas, Universidade Federal de Santa Catarina and Universidade Federal do Rio Grande do Sul. The dataset obtained, prepared, and used in the present research is available for new studies.